Jahwe als Wettergott: Studien zur althebräischen Kultlyrik anhand ausgewählter Psalmen - Müller, Reinhard (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2008)
It has long been suspected that Yahweh, the God of the Old Testament, was originally a weather god of the same type as the Syrian Baal. The present study presents the exegetic basis for this. It demonstrates how the Psalter preserves various ancient cultic songs praising Yahweh as a royal weather god. Parallels in Syrian and Mesopotamian weather god traditionsshow that originally the Ancient Hebrew notion of God was not fundamentally different from that of its surroundings